PENTINGNYA PENDIDIKAN KEWARGANEGARAAN DI ERA GLOBALISASI DALAM MENCEGAH DEGRADASI MORAL - Siti Fadia Nurul Fitri; Dinie Anggraeni Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Globalization is a process where there is rapid development in various fields, especially in the fields of technology and communication. Globalization can be likened to two sides of a coin. This means that globalization has a positive impact as well as a negative impact. The positive impact of globalization makes things easier. Meanwhile, the negative impact that often occurs is the moral degradation of a nation. This study aims to determine the importance of Citizenship Education in this era of globalization as an effort to prevent moral degradation among millennials. The research method used is literature review research methods sourced from scientific articles, scientific journals, and research results in the form of theses, books, internet, and other relevant sources.